“They have no limits”: Territory, borders and inequality in the (in)tense relationship between São Conrado and Rocinha - O'Donnell, Julia Galli (2024)
This article analyzes, from a historical-processual perspective, the relationship between the neighborhoods of São Conrado and Rocinha, located in the south of Rio de Janeiro. With research based on newspaper articles and a group of messages from São Conrado residents, the text reflects on the representations produced about the two neighborhoods over time, paying attention to how they produce forms of occupation and experimentation with space, at the same time as they are produced by them. This study considers the many limits of a dichotomous view of these neighborhoods, revealing the many forms of intertwining and dispute that mark the process of producing shared urban space.